Reconstruction of parent microstructures in TRIP titanium alloys. (15th March 2023) - Saville, Alec I.; Ellyson, Benjamin; Eres-Castellanos, Adriana; Benzing, Jake T.; Clarke, Amy J.
Abstract: The metastable β -Ti alloy Ti-10V-2Fe-3Al (wt%) exhibits transformation induced plasticity (TRIP) (or the transformation of the parent β phase to product martensite) and desirable work hardening characteristics. However, the majority of the parent β -Ti microstructure is transformed into α ″ martensite during deformation by TRIP, obscuring how parent grain orientations influence the deformation behavior. This work demonstrates the successful reconstruction of parent β -Ti orientations from partially transformed microstructures consisting of remnant β -Ti and α ″ martensite. Reconstruction was completed using experimentally derived crystallographic orientation relationships (ORs) and a new, computationally derived OR of equivalent nature. Despite the two ORs being crystallographically identical, the reconstructed β -Ti microstructures showed significant differences, showcasing sensitivities that can be present in the reconstruction of parent phases with less common ORs. Regardless of this difference, the demonstrated ability to reconstruct β -Ti microstructures from partially transformed microstructures enables the calculation of orientation specific properties of deformation mechanisms in Ti-10V-2Fe-3Al. Graphical abstract: Image, graphical abstract